2004
DOI: 10.1093/humrep/deh319
|View full text |Cite
|
Sign up to set email alerts
|

An economic comparison of a laparoscopic electrocautery strategy and ovulation induction with recombinant FSH in women with clomiphene citrate-resistant polycystic ovary syndrome

Abstract: The total treatment costs up to an ongoing pregnancy are comparable for rFSH treatment and an alternative strategy starting with electrocautery. Due to a lower number of multiple pregnancies, the electrocautery strategy can be expected to result in lower total costs when costs of the delivery are included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…In this regard, treatments used in PCOS patients by ameliorating the clinical aspects and preventing the long-term consequences of the disease could improve their QoL. Presently, few data (358,362,363) have evaluated the impact of specific treatment on QoL in PCOS patients.…”
Section: Quality Of Life Impairmentmentioning
confidence: 99%
“…In this regard, treatments used in PCOS patients by ameliorating the clinical aspects and preventing the long-term consequences of the disease could improve their QoL. Presently, few data (358,362,363) have evaluated the impact of specific treatment on QoL in PCOS patients.…”
Section: Quality Of Life Impairmentmentioning
confidence: 99%
“…In women under treatment, the use of gonadotrophins was slightly more burdensome than LEO. Because of a lower number of multiple pregnancies, the LEO strategy can be expected to result in fewer obstetric complications and lower total costs if delivery costs are included in the economic analysis [19].…”
Section: Integrating Results and Making A Decisionmentioning
confidence: 99%
“…In contrast, van Wely et al [9] found a comparable societal cost up to an ongoing pregnancy between the two treatment strategies, and Farquhar et al [8] concluded that LOD was the least expensive option in CC-resistant PCOS patients. Both studies also used a societal approach.…”
Section: Discussionmentioning
confidence: 99%
“…These treatments have been proven to be effective but entail significant costs and possibly short- and long-term complications [4,5,6,7]. In 2004, two health-economic evaluations from a societal perspective comparing both treatment strategies were published [8,9]. Farquhar et al [8] concluded that LOD was the most cost-effective option, whereas van Wely et al [9] found that both treatments had a comparable cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation